Effect of Industrial Effluent on the Groundwater Quality in Haridwar - Shalini; Sharma, Pradeep Kumar; Naithani, Pratibha (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*289.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93648);" role="presentation">A study was conducted in Haridwar to evaluate the effect of industrial effluent on groundwater. A total number <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*302.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974306);" role="presentation">of seven water samples were considered, five <span dir="ltr" style="left: calc(var(--scale-factor)*273.65px); top: calc(var(--scale-factor)*302.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971653);" role="presentation">samples were collected from State Industrial Development <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*315.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930688);" role="presentation">Corporation of Uttarakhand Limited (SIDCUL) and two ground water samples were collected from Salempur, a <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*329.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924895);" role="presentation">village situated nearby SIDCUL, Haridwar. Samples were analyzed for parameters such as pH, Tot<span dir="ltr" style="left: calc(var(--scale-factor)*473.50px); top: calc(var(--scale-factor)*329.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928104);" role="presentation">al Dissolved <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*342.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942046);" role="presentation">Solids (TDS), Total Suspended Solids (TSS), Total Solids (TS), total hardness, electrical conductivity, salinity, <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*355.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978938);" role="presentation">Lead (Pb), Chromium (Cr), Arsenic (As), Iron (Fe), Aluminium (Al), Manganese (Mn) and Nickel (Ni). The <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*368.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917963);" role="presentation">results were compared with <span dir="ltr" style="left: calc(var(--scale-factor)*186.29px); top: calc(var(--scale-factor)*368.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922609);" role="presentation">limits prescribed by Bureau of Indian Standards. It was observed that ground water <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*382.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9489);" role="presentation">near the industrial area has been polluted. It can be concluded from the study that waste water of industry is <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*395.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915464);" role="presentation">affecting the ground water quality and thus posing a major th<span dir="ltr" style="left: calc(var(--scale-factor)*316.51px); top: calc(var(--scale-factor)*395.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92012);" role="presentation">reat to health of the people living in Salempur.